Folk dance as a pedagogical strategy for educational inclusion. (The Voz a Vos Bulletin, 2025)
The purpose of this research is to design a pedagogical strategy based on folk dance that promotes the integral development of students with disabilities from eighth to eleventh grade at Miguel Antonio Caro Educational Institution in Funza, Cundinamarca. Inclusive education in Colombia, supported by regulations such as the General Education Law 115 of 1994 and Decree 1421 of 2017, poses the challenge of ensuring meaningful learning and the full participation of all students in regular school environments. In this context, the institution has implemented folk dance as a pedagogical strategy that not only fosters the development of motor, cognitive, and socio-emotional skills.The methodology adopted corresponds to the systematization of experiences under the qualitative paradigm, following the proposal of Jara (2001). For this purpose, techniques such as participant observation, interviews with teachers and students, and the analysis of institutional records and community workshops are employed. This approach allows for the reconstruction and analysis of the process that began in 2009, when the institution integrated students with disabilities into regular classrooms, encouraging active participation and coexistence.Partial results show that folk dance has contributed to social inclusion, emotional development, and the strengthening of values such as respect, solidarity, and empathy among both students with disabilities and their peers. Thus, this research provides a practical and contextual contribution to inclusive education in Colombia, demonstrating that art, and particularly dance, can be a driving force for pedagogical and social transformation.
Keywords: Inclusion; Folk dance; Disability; Strategy; Systematization